Soil Quality and Enhanced Productivity through Soil Organic Matter - Rao, P. Chandrasekhar; Padmaja, G. (International Journal of Economic Plants, 2016)
Soil quality and health of the soil is a very important factors for growing of crops. The accelerated decomposition of soil organic carbon due to agriculture, resulting in loss of carbon to atmosphere and its contribution to greenhouse effect is a serious problem. Important factors controlling soil SOM status include climate, especially rainfall and temperature hydrology, parent material, soil fertility, biological activity, vegetation and land use. Assessment of soil quality, which is ‘the capacity of the soil to produce safe and nutritious food, to enhance human and animal health and overcome degradative processes” is thought to be a means to maintain soil health and quality. There is no doubt that agricultural management practices such as crop rotations, inclusion of legumes in cropping systems, addition of animal based manures, adoption of soil water conservation practices, various permutations and combinations of deep and shallow tillage, mulching of soils with insitu grown and external plant and leaf materials were part and parcel of agriculture in India. Despite all these efforts, the concept of conservation farming could not be followed in an integrated manner to except greater impact in terms of protecting the soil resource from degradative processes. One of the approaches could be better land husbandry (BLH). It is an integrated and synergistic resource management. Components of BLH are Build up SOM and related biological activity, Integrated plant nutrition management, Better crop management, Better rainwater management, improved soil structure for better rooting depth and permeability, adoption of people centred learning approach and community based participatory approaches.